Enhancement of block chain security using re authentication of digital signatures - Rajasekhar, K; Raga Rohith, N; N V Krishna Mohan, G; Divya, D; Jaya Bharathi, Ch (International Journal of Engineering and Technology, 2017)
Block chain technology first got confined to crypto currencies but later has seen its image in varied applications and hence there is a lot of need to improve its security according to the application. Because of the current digital world revolution there are both the need of its implementation for safe and secure transactions, implementations and at the same time the threats it has been facing day by day. This also could be more efficiently implemented when there is a regulating authority set over for the whole network to whom a particular user can ask to if there is any problem. In this paper we are going to see mainly about the working of block chain technology and security threats of block chain and how can we overcome one of the threats i.e 51% attack. We also are going to see its varied applications in different fields and types of block chains which can be implemented in different applications.